The Use of English on Linguistic Landscape in Tulungagung: The Initial Evidence of Language Battle in Public Space - Sasa Lailatul Fitria; Slamet Setiawan (e-Journal of Linguistics, 2023)
The widespread use of English is depicted in the LinguisticLandscape (LL) in Tulungagung competes the Indonesianlanguage (the national language) and Javanese language (thelocal language). The present study is aimed (1) to view theposition of English language among the existing languages, (2) toinvestigate what motive that urges a signage owner in acquiringEnglish, and (3) to explain the role performed by English insociety. A descriptive qualitative method in research is carried outto explain the phenomenon. Data were collected from anobservation of languages appear on signage and an interview tothe signage owner. This study is set up in Tulungagung Regencythat characterized as the Central Business District (CBD). Fromthe total 460 photographed signages observed and the interviewsdone, it is shown that English in society is not more dominant thanthe Indonesian language in use as explained by Landry & Bourhis(1997) but as the interviews done with the signage owner, itnarrates that English carries some characterization proposed byPiller (2001) that urge a party to acquire English and it also playssignificant roles in society, specifically in business field as statedby Lee (2019). Thus, it challenges the use of local language, theJavanese language, since English appears within its excellence.